The Effect of Translucency and Surface Treatment on the Flexural Strength of Aged Monolithic Zirconia - Rashin Giti; Benika Abbasi (International Journal of Dentistry)
Aims. This in vitro study aimed to evaluate the effect of the degrees of translucency in different types of monolithic zirconia as well as the aging and surface treatment with airborne particle abrasion on the flexural strength of monolithic zirconia. Materials and Methods. Sixty bar-shaped specimens were fabricated from three different types of presintered monolithic zirconia (n = 20 per group) including low translucent (LT) (DD Bio ZW iso, high strength zirconia, Dental Direkt, Germany), high translucent (HT) (DD Bio ZX2 98, high translucent zirconia, Dental Direkt, Germany), and multilayered system (ML) (DD cubeX2®ML, multilayer, cubic zirconia system, Dental Direkt, Germany). Each monolithic zirconia group was equally subdivided according to be either air-abraded with 110 µm aluminium oxide particles or left untreated (control). After thermocycling, the flexural strength was measured by using a universal testing machine. Two-way ANOVA followed by Tukey’s post hoc and independent samples t-test were used for the statistical analyses (P < 0.05). Results. Surface treatment and types of zirconia were found to have a significant interaction (P = 0.010). Having controlled the effect of surface treatment, the flexural strength of HT and LT zirconia was found to be significantly higher than the ML zirconia system (P ≤ 0.001). Airborne particle abrasion could significantly decrease the flexural strength of monolithic zirconia only in ML zirconia (P = 0.002). Conclusions. Multilayered zirconia system had the lowest flexural strength among all groups. Moreover, the flexural strength of this system was attenuated by surface treatment with airborne particles abrasion.